Relationship between risky behaviors and non-prescription opioid use among Asian American youth. Issue 1 (1st March 2022) - Weerakoon, Sitara M.; Keeton, Juang M.; Vidot, Denise C.; Arheart, Kristopher L.; Messiah, Sarah E.
Abstract: Asian Americans (AA) are a highly understudied population and are often considered the "model minority" for health. However, there is a dearth of research on risky behaviors associated with opioid use in AA teens. Data among AA youth aged 12 to 16 was collected from the 2017 Youth Risk Behavior Surveillance System. Multivariate logistic regression models were run to determine associations between opioid use and risky behaviors, controlling for age and sex. Findings showed that opioid use is significantly associated with weapon carrying, risky sexual behavior, and body image. These conclusions inform public health practice on substance abuse treatment in AA teens.